2015
DOI: 10.1007/s13165-015-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

How to understand the complexity of product quality and the challenges in differentiating between organically and conventionally grown products—exemplified by fresh and heat-processed carrots (Daucus carota L.)

Abstract: Quality traits are highly focused upon in the marketing of organic food products. There is a need to define and measure quality as consumers seem to have preconceived notions about the superior health value and taste of organic compared to non-organic products. A commonly held opinion among many consumer groups is that organic farming guarantees optimum quality, despite the fact that this remains unproven. The aim of this paper is to contribute to a better understanding of the complexity of quality traits in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…7 ). The consumers’ belief that organic food is a safer alternative is not supported by science due to the lack of consistent scientific evidence for generalizing such superiority [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 ). The consumers’ belief that organic food is a safer alternative is not supported by science due to the lack of consistent scientific evidence for generalizing such superiority [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent European-wide study detected pesticide residues in over 80% of the tested agricultural soils [19]. Therefore, synthetic pesticide residues in vegetables have become a special concern, not only due to potential negative influences on soil microorganisms and human health, but also in terms of consumer expectations [20,21]. According to Seufert and Ramankutty [2] the majority of studies have found that, compared to conventional production, organically produced food, indeed, has reduced contamination from pesticide residues.…”
Section: Introductionmentioning
confidence: 99%